Hoax and new media: content analysis of news about hoax in www.viva.co.id - Monika Sri Yuliarti (Penerbit Universiti Kebangsaan Malaysia, 2018)
Media is a source of information for the people. Since the emergence of the Internet, the role of new media got more important, since it has the ability to disseminate the information faster and wider. In media industry, the number of online news site increases along with the development of internet users. This online news sites cover all of the themes that interesting for the readers. Hoax has been a crucial topic appears in the news, whether in traditional mass media or online media. This study aims to reveal the news about hoax in an online news site, namely www.viva.co.id. It is important, since hoax is an inevitable phenomenon in the internet era, and the online news site belongs to one of the candidates for president of Indonesia when the election happened in 2012. The data gathered using observation toward the online news site in the period of 2016, specifically the news about the hoax. Observation toward the data was also being done to get the right data. Meanwhile, the analysis technique employed in this study is content analysis. The finding shows that there is a small number of news about hoax in 2016. They tend to be neutral for the tone of the news. This finding is interesting since the owner of the media is a politician that was also a president candidate in the former general election.